Development of alternatives to estimate resting metabolic rate from anthropometric variables in paralympic swimmers - Herrera-Amante, C. A.; Ramos-García, C. O.; Alacid, F.; Quiroga-Morales, L. A.; Martínez-Rubio, A. J.; Bonilla, D. A. (Journal of Sports Sciences, 2021)
The resting metabolic rate (RMR) is one of the most representative components of total daily energy expenditure (TDEE). Multiple equations have been developed to estimate RMR, but none have been described for Para-Athletes. This study aimed to; i) develop and validate new RMR estimation models from anthropometric variables; and ii) explore the level of agreement between the RMR determined by indirect calorimetry (IC) and the developed models, as well as a selection of existent estimation models in Para-Athletes. Fifteen young Paralympic swimmers (age, 18.7±6.5 years) underwent assessments of RMR by IC and anthropometric batteries. Four RMR estimation models (M1-M4) were developed. The anthropometric variables which explained most of the variance were biacromial breadth (M3-37%), stature (M1-45%; M2-49%), and estimated stature from half arm span (M4-24%). However, the neck girth corrected by the submandibular skinfold entered in all four models. The 95% limits of agreement between IC and M3 equation (best performance model) ranged from -142.02 to 172.39 kcal×day-1 (bias 15.19 kcal×day-1). Concerning the commonly used equations, Harris & Benedict equation was the most consistent when compared to IC. The results of this study suggest four novel RMR equations that may assist in the estimation of energy requirements in elite Para-Athletes.